“I Hate to Be Evaluated”: A Grounded-Theory Analysis of Adult Learners‟ Evaluation Anxiety in Korea National Open University - K.P. Joo (Adult Education Research Conference, 2012)
Drawing upon the grounded-theory approach, this research examines how adult learners in Korea National Open University (KNOU) experience evaluation anxiety through centralized institutional examination activities. The final model categorizes conceptions of personal, institutional, and socio-cultural origins and patterns of apprehension and anxiety in relation to evaluation. Keywords: Evaluation Anxiety, Grounded-Theory, Open University.
Keywords: Evaluation Anxiety; Grounded-Theory; Open University